MEMBACA ADOPSI STANDAR PELAPORAN KEUANGAN DALAM PERSPEKTIF KUASA DAN PENGETAHUAN FOUCAULT - Febiyola Halan, Yohanes (Program Studi Akuntansi Universitas Panca Bhakti, 2024)
The adoption of financial reporting standards is approached in a different way in this research. The objective is to comprehend and clarify the adoption of financial reporting standards from the perspective of the power held by standard-setting bodies. The power they possess is connected to their knowledge. The researcher uses Foucault's power-knowledge relational perspective as the research method. The findings demonstrate a strong connection between power and knowledge when it comes to adopting financial reporting standards. Standard-setting bodies use their knowledge to exert power. Internalizing power in financial reporting standards leads to knowledge. Standard-setters have a non-oppressive and omnipresent power. This research is expected to provide a novel understanding of the adoption of financial reporting standards from the perspective of power-knowledge relations.